Chronostratigraphy and environment of Furnas Formation by trace fossil analysis: Calibrating the lower Paleozoic Gondwana realm in the Paraná Basin (Brazil) - Sedorko, Daniel; Netto, Renata G.; Savrda, Charles E.; Assine, Mario L. [UNESP]; Tognoli, Francisco M.W. (Elsevier, 2017)
Ichnology is an important tool for facies and sequence stratigraphic analysis, typically yielding greater resolution than that provided by body fossils. Less commonly, ichnofossils also can be applied to ichnostratigraphy, a variant of biostratigraphy that aids in determining stratigraphic age of sedimentary sequences. Previous publications on the Furnas Formation (Paraná Group, early Paleozoic of the Paraná Basin), have yielded different interpretations of age, depositional environment, and sequence stratigraphic framework. Deposition in fluvial environments has been proposed in many papers, although a tide-influenced marine context has been inferred since the presence of Cruziana and Rusophycus was reported during the 1990s. Sequence stratigraphic interpretations also differ, mainly regarding the presence or absence of a sequence boundary between the middle and upper units of the Furnas Formation. The absence of body fossils in all but the topmost part of the upper unit, which contains Lochkovian (Lower Devonian) palynomorphs and primitive plants, has precluded age determination for the Furnas Formation in general. Here, we demonstrate the utility of both ichnofacies and ichnostratigraphic analysis to elucidate such questions. The studied sections are located in the cities of Tibagi, Palmeira and Ponta Grossa (Guartelá, Sítio Canei and São Jorge sections, respectively). Seventeen ichnotaxa are recognized, doubling the number of previously known ichnotaxa: Cruziana acacensis elongata and Rusophycus acacensis n. ichnosp. (in the lower and middle units); Arthrophycus alleghaniensis, A. brongniartii, Rhizocorallium commune, Didymaulyponomos rowei and Heimdallia chatwini (middle unit only); Arenicolites, Cylindrichnus and Diplocraterion (lower and upper units); Lockeia siliquaria and Psammichnites implexus (middle and upper units); Rosselia socialis (upper unit); and Palaeophycus tubularis, Didymaulichnus lyelli, Skolithos, and Thalassinoides (all units). Assemblages of these ichnofossils are assigned to Skolithos and proximal Cruziana ichnofacies. Ichnologic data, combined with associated physical sedimentary facies associations, indicate predominantly tide-influenced marine depositional environments. The presence of ichnotaxa of stratigraphic value (Arthrophycus alleghaniensis, A. brongniartii and Cruziana acacensis elongata) in lower and middle units indicates an Early Silurian age. This, in turn, indicates that a significant unconformity exists between the middle and upper units of Furnas Formation. Although the precise magnitude of this stratigraphic gap is difficult to establish, this break likely is linked to the Late Silurian global regression.
Keywords: Cruziana ichnofacies; Devonian; Ichnostratigraphy; Silurian; Skolithos ichnofacies